Graphene nanoribbons as prospective field emitter - Khare, Ruchita T.; Shinde, Dhanraj B.; Bansode, Sanjeewani; More, Mahendra A.; Majumder, Mainak; Pillai, Vijayamohanan K.; Late, Dattatray J. (Applied Physics Letters, 2015)
Field emission characteristics of graphene nanoribbons (GNRs) synthesized by unzipping of multiwall carbon nanotubes using a facile hydrothermal route have been investigated at a base pressure of 1 x 10(-8) mbar. The values of turn-on field, required to draw an emission current densities of 1 and 10 mu A/cm(2), are found to be 2.8 and 5.8 V/mu m, respectively, and a maximum emission current density of 500 mu A/cm(2) has been drawn at an applied field of 9.8 V/mu m. The emission current stability of the GNRs emitter was studied at preset values of 1 and 10 mu A over a period of 3 h, and is found to be excellent. The field emission results demonstrated herein suggest that GNRs based field emitters can open up many opportunities for their potential utilization as large area field emitters in various vacuum micro-nanoelectronic devices such as flexible field emission displays, portable X-ray, and microwave tubes. (C) 2015 AIP Publishing LLC.